Augustine of Hippo faithful servant, spiritual leader. - Fitzgerald, Allan D.; Martin, Thomas F. O.S.A. (Boston Prentice Hall, 2011)
This work is meant for someone with little familiarity with Augustine of Hippo and his world. It is meant to introduce the reader to Augustine of Hippo and his thinking and to give the reader some 'direct' contact with him by keeping the focus on his own words. Some chapters conclude with an excerpt from Augustine's writings and others are heavily laden with Augustine's own words. Augustine dedicates an enormous amount of energy seeking to understand himself and exploring the 'human.' That intense interest on interiority has had a profound impact upon the West, leading commentators to attribute to Augustine the creation of the 'Western self.' His unique way of looking at and dealing with what it means to be human seems to place 'the self' at center stage and to prize highly introspection and reflection as ways to come to appreciate that 'self.' (Bron: http://www.pearsonhighered.com)
Keywords: Augustine, -- of Hippo, Saint, -- 354-430.; Christian saints -- Algeria -- Hippo (Extinct city) -- Biography; 276 =71 AUGUSTINUS <092> -- Latijnse patrologie--Biografieën--AUGUSTINUS